The Use of Banten-Dialect Javanese Language as the Identity Marker of Banten Society Viewed from Gender Perspective - Siti Suharsih (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2017)
Given the reality of language diversity in Banten and juxtaposed with the differences in language behavior between men and women, the researcher directly examined the pattern of Banten-Dialect Javanese Language associated with gender in the community of Gowok Village, Sukajaya, Curug District, Serang City. This study aimed to describe the patterns of Banten-Dialect Javanese Language use in the family and neighborhood domains viewed from gender perspective.To achieve the objectives, this study used a qualitative approach. A qualitative approach was used to describe the patterns of Banten-Dialect Javanese Language in two domains, namely family and neighborhood, and describe how gender can distinguish the use of language in the two domains. The populations of this research were the speakers of Banten-Dialect Javanese Language in Gowok Village, Curug District, Serang City, and the determination of sample as the respondents was done by snowball sampling technique. The method used to collect the data of this research was survey method. To obtain the data from large populations, the researcher used data collection techniques through a written questionnaire instrument .